Anesthetic management of a chronic liver disease patient with very low platelet counts by considering a rebalanced hemostasis - A case report - Han, Bobae; Lee, Suk Young; Kim, Gaab-Soo (Anesthesia and pain medicine (Korean society of anesthesiologists), 2018)
The coagulation profile of patients with end-stage liver disease (ESLD) is different from that of healthy individuals. Because hemostasis is rebalanced in chronic liver disease, prophylactic transfusion of blood products may be not necessary for these patients even if they show severe coagulation dysfunction in conventional coagulation results. A 44-year-old man with hepatocellular carcinoma, cholangiocarcinoma and liver cirrhosis was scheduled for extra-hepatic mass excision under general anesthesia. His preoperative tests showed severe thrombocytopenia 19 × 109/L. The patient underwent extrahepatic mass excision surgery under general anesthesia without transfusion of blood products. The post-operative course was uneventful without requiring any further hemostatic therapy. In this case report, we focus on the concept of rebalanced hemostasis in ESLD, and coagulation management based on rotational thromboelastometry. KCI Citation Count: 0